Global research trends in surgical management of choledochal cysts: a bibliometric analysis from 2000 to 2024 - Xingjian Liu; Guodong Zhu; Jiayi Zhang; Yulong Mu; Zongxing Qiao; Chuan Wang; Chuan Wang; Chuan Wang; Chuan Wang (Frontiers in Medicine, 2025)
IntroductionCholedochal cysts (CCs), which are congenital biliary anomalies prevalent in Asia, predominantly affect children and carry the risk of severe complications, including malignancy. Surgical intervention, evolving from open to minimally invasive (laparoscopic/robotic) techniques, remains the cornerstone of management. Despite growing research, no bibliometric analysis has mapped the global trends in CCs surgical studies. The aim of this study was to comprehensively analyze the advances in the surgical treatment of CCs since the 21st century and to predict future research directions.MethodsUsing the Web of Science Core Collection (2000–2024), we analyzed 1,064 publications on CCs surgery via Bibliometrix and CiteSpace. The search terms included surgical techniques (e.g., “laparoscop*,” “Roux-en-Y”) and disease terms (e.g., “choledochal cyst*”). The data encompassed authorship, citations, institutions, and keywords.ResultsAverage Annual publications increased by 5.95%, peaking by 2023 (n = 93). China (n = 579) and Japan (n = 398) dominated the research output, yet international collaboration was limited (MCP rate <10%). High-impact studies emphasized long-term malignancy risks after Roux-en-Y anastomosis and laparoscopic superiority over open surgery. Keyword analysis revealed shifting foci: “management” (n = 241) and “children” (n = 204) were predominant, while “robotic surgery” emerged post-2010. Institutions such as Monash University and the Capital Institute of Pediatrics led productivity, with the Journal of Pediatric Surgery being the top publisher.ConclusionSurging research on CCs surgery highlights evolving priorities: bibliometrics reveal a growing focus on long-term outcomes and minimally invasive techniques (laparoscopic/robotic). Enhanced preoperative and postoperative management and novel diagnostic methods are critical. Global collaboration and standardized training remain pivotal for optimizing patient prognosis.